Pengaruh Penggunaan Aplikasi Kahoot pada Mata Pelajaran Akidah Akhlak terhadap Peningkatan Hasil Belajar Siswa di MAS Tarbiyah Islamiyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The importance of education as a foundation for developing an intelligent and qualified generation, with an emphasis on Islamic religious education as a tool for shaping students' character and morals. Islamic religious education, particularly in the study of faith and morals, emphasizes ethical values ​​such as caring and honesty. With the challenges in education becoming increasingly complex, one example is that many educators are unable to utilize learning media in today's advanced technology. One proposed solution is the use of the digital platform Kahoot, which has been proven to attract student interest in learning faith and morals, overcoming the boredom often encountered with traditional methods, such as lectures. It is emphasized that schools need adequate facilities and strategies for using gadgets to enhance students' learning experiences.The quantitative method used in this study is a pre-experimental study. In this study, the researcher used the one-group pretest and posttest design model. Based on the research results, there was a pretest score with a mean of 93.46, a median of 95, and a mode of 95. The posttest score had a mean of 84.62, a median of 90, and a mode of 100. The sig. (2-tailed) table showed 0.002 with a research alpha of 5% or 0.005. It can be concluded that there is no effect because 0.002 < 0.005. Therefore, H1 is rejected. Therefore, there is no effect of using the Kahoot application on the subject of faith and morals on improving student learning outcomes at MAS Tarbiyah Islamiyah.